EFFECTIVENESS TEST OF BETEL LEAF FLOUR EXTRACT (Piper betle L.) ON LARVAE OF Helicoverpa armigera Hubner - Sutikno, Agus; Yudha, Pajri Ananta; Akbar, Adi (Universitas Veteran Bangun Nusantara, 2025)
Helicoverpa armigera is a major pest of maize crops and the losses caused by this pest are quite significant. Betel leaf is a part of plant that potential as botanical insecticide. The research aimed to examine several concentrations of betel leaf flour extract to control H. armigera. The research was conducted in Laboratory of Plant Pest, Faculty of Agriculture, Riau University from March to May 2023. Completely randomized design that consisted five treatments and four replicates was used as in the study. A completely randomized design (CRD) consisting of 5 treatments was used in this study. The treatments were flour extracts of betel leaf (0 g/l water, 25 g/l water, 50 g/l water, 75 g/l water and 100 g/l water). The result showed the concentration 75 g/l water was the effective treatment to control H. armigera larvae. The total mortality of H. armigera larvae in the treatment was 85% with early lethal time (LT) was 15.25 hours after application and lethal time 50 (LT 50) was 41 hours after application. Piper betel was a potential plant as botanical insecticide to control H. armigera.